2003
DOI: 10.1002/14651858.cd004014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of pelvic organ prolapse in women

Abstract: Background Pelvic organ prolapse may occur in up to 50% of parous women. A variety of urinary, bowel and sexual symptoms may be associated with the prolapse. Objectives To determine the effects of the many different surgeries used in the management of pelvic organ prolapse. Search methods We searched the Cochrane Incontinence Group Specialised Register (9 February 2009) and reference lists of relevant articles. We also contacted researchers in the field. Selection criteria Randomised or quasi-randomised contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…8,43,44 roovers et al 45 rEViEwS ligament complex. 45,46 recurrence was higher in the abdominal surgery group (22%) than in the vaginal hyster ectomy group (2.5%). Women who underwent abdominal sacrohysteropexy also reported more dis comfort caused by overactive bladder symptoms.…”
Section: Abdominal Approachmentioning
confidence: 82%
See 2 more Smart Citations
“…8,43,44 roovers et al 45 rEViEwS ligament complex. 45,46 recurrence was higher in the abdominal surgery group (22%) than in the vaginal hyster ectomy group (2.5%). Women who underwent abdominal sacrohysteropexy also reported more dis comfort caused by overactive bladder symptoms.…”
Section: Abdominal Approachmentioning
confidence: 82%
“…The results of com parison trials and prospective studies have confirmed that uterussparing surgery is feasible, with shorter oper ating times and hospital stays and similar outcomes com pared to hysterectomy. 33,46 Although the decision will be determined by the patient's preference and the surgeon's skills and experience, it is imperative that women fully understand the risks of incurring uterine and cervical pathology over time, and the need for continued routine surveillance measures to assess for such pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic organ prolapse (POP) is an important issue in women's health care, occurring in up to 50% of parous women [1,2]. POP negatively impacts health-related quality of life by affecting daily activities, body image, and sexual function [3].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35] In women undergoing prolapse repair surgery in whom SUI is preexisting, there is uncertainty as to whether a continence procedure such as suburethral tapes should be performed at the same time. 36,37…”
Section: Discussionmentioning
confidence: 99%